Performance of compliant mechanisms applied to a modified shape accelerometer of single and double layer - Margarita Tecpoyotl-Torres; Ramon Cabello-Ruiz; Pedro Vargas-Chable; Jose Gerardo Vera-Dimas; Alejandra Ocampo-Diaz (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Accelerometers are widely used in several mechanisms of high sensitivity. They are employed for example in tilt-control in spacecraft, inertial navigation, oil exploration, seismic monitoring, etc. In order to improve the sensitivity of the measurements, implementation of Displacement-amplifying Compliant Mechanisms (DaCMs) in a capacitive accelerometer have been reported in the literature. In this paper, a system composed of two elements; capacitive accelerometer with extended beams (CAEB) and a DaCM geometry, of single and souble layer, are analysed. Three materials were considered, in the case, for the second layer. The DaCM implementation improves the operation frequency and displacement sensitivity, under different proportions, at the same time. Furthermore, three sweeps were performed: a range of thickness from 25 µm up to 30 µm (to determine the appropriate silicon mass value, using SOI technology), a range of second layer thickness (to choose the more appropriate material and its thickness) and a range of gravity values (to determine the maximum normal stress in the beams, which defines the superior value of the g operation range). The in-plane mode (y-axis) was considered in all analysed cases. This characterization was developed using the Finite Element Method. Structural and modal analysis responses were under study.